2019
DOI: 10.1080/15332640.2019.1568335
|View full text |Cite
|
Sign up to set email alerts
|

Using a fotonovela to battle crystal meth in South Africa

Abstract: This study evaluated the effects of a health-related fotonovela about crystal meth (S-methamphetamine hydrochloride) among "Colored" people (an ethnic label for people of mixed race) in the Western Cape province of South Africa. Crystal meth use is most common among Colored people in this province and it is considered a major social problem. The fotonovela was compared to a no-message control group and a traditional brochure in a randomized controlled trial (N ¼ 303). The fotonovela outperformed the control co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…Similar outcomes are reported in a recent quantitative study in South Africa into the effects of a health-related photo story about crystal meth compared to a non-narrative brochure based on two existing traditional crystal meth documents [19]. In that study, the photo story on the dangers of crystal meth did not outperform the non-narrative brochure on knowledge or attitude.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar outcomes are reported in a recent quantitative study in South Africa into the effects of a health-related photo story about crystal meth compared to a non-narrative brochure based on two existing traditional crystal meth documents [19]. In that study, the photo story on the dangers of crystal meth did not outperform the non-narrative brochure on knowledge or attitude.…”
Section: Discussionsupporting
confidence: 80%
“…While no significant differences were found in effects related to action (self-efficacy and behavioral intention), the difference we did find in motivation (preference) suggests that in a natural context people might be more willing to read the photo story booklet than the non-narrative brochure. Evidently, willingness to read a given document is a necessary, though under-researched condition for any processing effect to occur (see also [19]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that a specific form of narratives, namely ‘photo stories’ may be particularly effective health communication tools, especially for readers with a low level of literacy [ 23 , 32 , 33 , 34 , 35 , 36 ]. Photo stories, also called “fotonovelas”, are small publications, often in booklet format, that tell a (dramatic) story by means of photographs and short and easily readable captions.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated presentation of textual and visual information in photo stories minimizes cognitive load, thus supporting information processing and learning [ 37 , 38 ]. Studies comparing photo stories to more traditional formats for health communication revealed only small effects on knowledge, attitudes and behavioral intentions, but readers clearly found photo stories more appealing [ 36 , 39 ].…”
Section: Introductionmentioning
confidence: 99%